METODE MUHADDITSIN DI ERA MODERN - Adriansyah, Adriansyah (Jurnal Ushuluddin, 2016)
After the era of tadwin, almost all disciplines of knowledge in the Islamic world, including the study of hadith, was considered ârunning on the spot.â Yet, attention and maintenance of the hadith was still favored by intellectuals. Similarly, in the modern era, the hadith remains the object of criticism by not only Muslim intellectuals but also outsiders, such as the West. Western imperialism against the Islamic world in the past was now the beginning of the history of how Muslims are only able to âsurviveâ rather than âattack.â The emergence of defensive and reactive works against trends of the West in criticizing and blasphemed the hadith, then, such works became trends and supporting methodologies among Muslim observers of the hadith in todayâs modern era